Disease‐specific mutations in mature lymphoid neoplasms: Recent advances. Issue 6 (12th May 2014) - Sakata‐Yanagimoto, Mamiko; Enami, Terukazu; Yokoyama, Yasuhisa; Chiba, Shigeru
<x xml:space="preserve">Abstract</x> Mature lymphoid neoplasms (MLN) are clinically and pathologically more complex than precursor lymphoid neoplasms. Until recently, molecular characterization of MLN was mainly based on cytogenetics/fluorescence in situ hybridization, allele copy number, and mRNA expression, approaches that yielded scanty gene mutation information. Use of massive parallel sequencing technologies has changed this outcome, and now many gene mutations have been discovered. Some of these are considerably frequent in, and substantially specific to, distinct MLN subtypes, and occur at single or several hotspots. They include the V600E BRAF mutation in hairy cell leukemia, the L265P MYD88 mutation in Waldenström macroglobulinemia, the G17V RHOA mutation in angioimmunoblastic T‐cell lymphoma and peripheral T‐cell lymphoma, not otherwise specified, and the Y640F//D661Y/V/H/I//N647I STAT3 mutations in T‐cell large granular lymphocytic leukemia. Detecting these mutations is highly valuable in diagnosing MLN subtypes. Defining these mutations also sheds light on the molecular pathogenesis of MLN, furthering development of molecular targeting therapies. In this review, we focus on the disease‐specific gene mutations in MLN discovered by recent massive sequencing technologies.